A retrospective analysis of prenatal genetic results in fetal hydronephrosis - Keqin Jin; Xiayuan Xu; Yue Qian; Liping Zhang; Min Hu; Jianfeng Luo (PLoS ONE, 2025)
Objective To discuss the application value of technologies such as chromosome microarray analysis (CMA) in fetuses with hydronephrosis and pyelectasis. Methods Retrospectively collected the prenatal diagnostic data of 83 fetuses with hydronephrosis from January 2020 to July 2024. The positive rate of chromosomal abnormalities detected by different ultrasound abnormalities was statistically analyzed. Results Among the 83 pregnant women, 10 cases of abnormal karyotypes were detected by invasive prenatal diagnosis, with an abnormality rate of 12.05%. Numerical chromosomal abnormalities accounted for 90%, mainly trisomy 21 and 13. In the fetuses with normal karyotype/no abnormality, CMA additionally detected 15 copy number variations (CNVs) in 12 cases. Divided into isolated hydronephrosis and non-isolated hydronephrosis groups, the detection rates of fetuses carrying pathogenic CNVs were 5.56% and 12.77% respectively, and the detection rates of fetuses carrying variants of uncertain significance (VUS) were 19.44% and 8.51% respectively. Still, the differences between the two groups were not statistically significant (P > 0.05). Divided into moderate to severe hydronephrosis group and mild hydronephrosis group, the detection rate of pathogenic abnormalities by CMA was 10% and 37.21% respectively, and the difference between the two groups was statistically significant (P < 0.05). Conclusion Hydronephrosis is associated with chromosomal abnormalities, and the rate of chromosomal abnormalities increases significantly as the degree of hydronephrosis increases. The combined use of CMA technology can detect abnormalities caused by chromosomal microdeletions and/or microduplications, which is of great value for clinical prenatal consultation.